Boosting the efficiency of aqueous solar cells: A photoelectrochemical estimation on the effectiveness of TiCl4 treatment. (10th April 2019) - Bella, Federico; Galliano, Simone; Piana, Giulia; Giacona, Giulia; Viscardi, Guido; Grätzel, Michael; Barolo, Claudia; Gerbaldi, Claudio
Abstract: Increasing the photocurrent is one of the main objectives of the current research on aqueous photovoltaic cells, the emerging green, alternative technology in solar energy conversion devices. In such a scenario, this work deals with the thorough understanding of the electrochemical and photoelectrochemical effects of the TiCl4 treatment onto TiO2 electrodes, a well-known process for traditional dye-sensitized solar cells, and here, to our knowledge, investigated for the first time in water-based systems. From the quantitative evaluation of the photoelectrochemical parameters, it emerges that the TiCl4 treatment beneficially affects the photovoltaic parameters: it doubles the sunlight conversion efficiency values, inhibits the recombination of photogenerated electrons with oxidized redox mediator ions, and ensures stable and reproducible cell performance at the laboratory scale. Graphical abstract: Image 1 Highlights: TiCl4 treatment carried out to boost the efficiency of aqueous solar cells. The treatment doubles the sunlight conversion efficiency values up to 2.5%. Recombination of photogenerated electrons is strongly inhibited (OCVD/EIS study). 100% water-based solar cells without additives or heavy metals. Cells are very stable: +8% efficiency after 16 days of aging.